Digital Transformation and Corporate Innovation: Empirical Discovery Based on Machine Learning - Tingqian Pu,; Yujie Li,; Abdul Hadi Zulkafli , (Asian Academy of Management Journal of Accounting and Finance, 2024)
With the flourishing development of the digital economy, the phenomenon of digital transformation at the firm level has attracted scholars’ attention regarding its impact on microeconomic activities. However, whether the transformational changes induced by digital technologies affect corporate innovation and the underlying mechanisms have not been fully explored. Based on panel data from Chinese listed firms spanning from 2012 to 2021, this paper constructs a measure of digital transformation using machine learning techniques and investigates its relationship with corporate innovation. The findings suggest that digital transformation effectively promotes corporate innovation, a result robust to a battery of sensitivity checks. Mechanism analysis reveals that digital transformation significantly enhances innovation by increasing R&D input and improving innovation efficiency. Further analysis indicates that the innovation-promoting effect of digital transformation is mainly manifested in high-quality innovation output, with greater benefits observed for state-owned enterprises and non-high-tech industry enterprises. Overall, our study provides valuable policy insights for enhancing innovation levels among enterprises in developing countries like China through digital transformation strategies.